Methane emissions: from blind spot to spotlight - Le Fevre, C (Oxford Institute for Energy Studies, 2017)
The environmental impact of methane emissions – which come from a wide range of natural and anthropogenic sources – has received growing attention. Methane is a potent greenhouse gas (GHG). Methane emissions that occur across the gas supply chain have long been seen by the industry as an unfortunate, if necessary, part of doing business. The economic cost of this activity was recognised but the cost of reducing emissions often outweighed any benefit. Furthermore, many regulatory regimes included allowances for unaccounted for gas allowed operators to pass on the cost of emissions to consumers. The environmental impact of gas emissions was at best a minor consideration and in most cases an industry blind spot. Global ambient methane levels have been rising and the coinciding growth in global gas production – and the rise of unconventional gas and hydraulic fracturing – led some to conclude that methane emissions from the natural gas industry were primarily responsible. This hypothesis received further support in 2016 when the US EPA published a major upgrade (subsequently partially reversed) in emission estimates from natural gas supply. Furthermore, the gas industry’s track record in monitoring, reporting, and controlling methane emissions is arguably patchy. Industry attempts to present a united front have often resulted in obscure debates over data and impact. This has led environmental groups and some government agencies to question the, hitherto largely unchallenged, environmental credentials of natural gas as the “greenest” fossil fuel. In turn this resulted in increased demand for reporting and control requirements and greater industry focus, though initiatives have varied widely around the world. This paper summarises the main issues relating to gas industry methane emissions and examines the various activities, underway and planned, to assess and reduce them. It attempts to take a wide ranging, non-specialist, overview that covers both the technical and scientific perspectives as well as operational and regulatory considerations. The paper is structured as follows: The global picture for methane emissions and the part played by the energy sector Why controlling and reducing methane emissions is important. How methane emissions are measured and reported levels and sources for the energy and gas sectors How the impact of methane emissions is assessed The overall impact of methane emissions on the environmental case for natural gas Company and regulatory responses to the challenges of methane emissions It looks at the issues globally though to provide greater granularity and illustrate some of the key points includes country profiles of the USA and Great Britain.